Pendampingan Pembuatan LKS Berorientasi Metakognisi Pada Guru Sekolah Dasar Muhammadiyah 5 Batu - AM, Ichsan Anshory; Amelia, Delora Jantung; Saputra, Setiya Yunus (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2019)
Implementation, Community Service Program With the Title "Ibm Assistance Group for Making LKS Based on Metacognition in Elementary School Teachers" begins with a workshop providing material for making worksheets and material on metacognition. This activity involved collaboration with partner schools namely SD Muhammadiyah 5 Kota Batu. In this service the teacher appointed was all teachers ranging from class I teachers to class VI teachers, the principal of Muhammadiyah 5 Elementary School also participated in this activity. For the sake of the creation of this service program, all teachers need to gain reinforcement of concepts and material about making worksheets, learning activities and practice questions that are oriented to metacognition, with the provision of material reinforcement the optimal LKS will be made. Furthermore, the activities carried out were assisted in making LKS. This activity was carried out by the way the dedication team came to partner schools. The dedication team checks the drafts made by the teachers, sees the progress that has been made, and discusses the obstacles faced by the teacher in preparing the LKS. The worksheets produced here are metacognitive-oriented LKS so that all activities in the LKS must reflect LKS-oriented activities starting from their activities and the questions in them. As the end of the series of programs, this service is the gathering of LKS oriented to metacognition. LKS collected is LKS that has been checked by the service team and has been revised by the teachers. Improvement notes are discussed together, with the aim of preparing a follow-up plan.